MODEL PEMBELAJARAN PERSONAL DALAM PEMBELAJARAN DI SEKOLAH DASAR: PRINSIP, KARAKTERISTIK UMUM DAN IMPLIKASINYA TERHADAP PENGEMBANGAN DIRI SISWA - Winda Zunur Ain (Jurnal Komunikasi, 2026)
Personalized learning is an approach that adapts the learning process to each student’s needs, interests, and abilities. This paper aims to explain the principles, characteristics, and impact of personalized learning on elementary school students’ development. The method used is a literature review based on relevant sources. The results show that personalized learning emphasizes individual uniqueness, the teacher’s role as a facilitator, and active student involvement in learning. Its main characteristics include flexible instruction and learning adjusted to students’ abilities. This approach can help improve students’ independence, self-confidence, and responsibility in learning.